Reconstruction of the lncRNA-miRNA-mRNA network based on competitive endogenous RNA reveals functional miRNAs and lncRNAs in burns and keloids - Yueru Wang; Zhichao Wang; Jiaojiao Pan; He Wang; Ziwen Lei; Jing Liu; Junbo Zou; Haizhen Lv; Fei Luan (PLoS ONE, 2025)
Backgrounds Long non-coding RNAs (lncRNAs) exert their pharmacological functions by serving as sponges for related microRNAs (miRNAs), thereby modulating gene expression. Nevertheless, the regulatory roles of the lncRNA-mediated competing endogenous RNA (ceRNA) mechanism in the interplay between burns and keloids remain largely elusive. Objective To construct the ceRNA regulatory network of burns, leveraging network pharmacology and bioinformatics analyses. Results 3576 DELs (Differentially Expressed lncRNAs), 1427 DEMis (Differentially Expressed miRNAs), and 2555 DEMs (Differentially Expressed mRNAs) were identified as differentially expressed genes. A ceRNA network composed of DELs-DEMis-DEMs in burns and keloids was constructed, with a prominent sub-network consisting of 23 DELs, 330 DEMs, and 8 DEMis. Subsequently, the clusterProfiler package in the R programming language was utilized to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. The sub-network within the ceRNA network was extracted, in which three lncRNAs, namely lnc-WRB, lnc-SCNN1G, and LINC00271, and three miRNAs, namely hsa-miR-21, hsa-miR-34a, and hsa-miR-155, were identified as key genes. Conclusion All nodes within the sub-ceRNA network exert either a direct or an indirect influence on the pathological processes of burns and post-burn keloids. The current study successfully constructed the ceRNA network in burns and keloids and provided a potentially novel perspective on the DELs-DEMis-DEMs ceRNA network, contributing to the elucidation of the ceRNA regulatory mechanisms in the pathogenesis of burns and keloids. Nevertheless, systematic and rigorous experimental validations are indispensable to confirm our findings.